Curative‐intent treatment of pulmonary metastases from colorectal cancer: A comparison between imaging‐guided thermal ablation and surgery. Issue 1 (28th September 2022) - Karam, Elias; Tabutin, Mayeul; Mastier, Charles; Crignis, Lucas De; Peyrat, Patrice; Martin, Valentine; Badon, Floriane; Muller, Xavier; Meeus, Pierre; Rivoire, Michel; Dupré, Aurélien
Abstract: Background: Pulmonary metastases (PM) are the most frequent extra‐abdominal metastases from colorectal cancer. Lung resection and imaging‐guided thermal ablation (IGTA) are used as curative‐intent treatment. We compared the outcomes of patients with PM, treated with resection or ablation. Methods: We retrospectively analyzed data from patients who underwent surgery or IGTA for colorectal PM between April 2011 and November 2020. Surgery was performed for peripheral PM and IGTA for deep‐located PM not in contact with major vessels. Patients who had both procedures were excluded. Patients were compared using propensity score matching (PSM) analysis, stratified according to number, size, and unilaterality of PM. Results: One hundred and fourty‐six patients were included, 65 (44.5%) underwent surgery and 81 (55.5%) underwent IGTA. After PSM analysis, each group contained 46 patients. IGTA patients had a lower morbidity rate (13.1% vs. 15.2%, p  = 0.028) and a shorter length of stay (5.13 vs. 2.63 days, p  < 0.001). Oncological outcomes were similar in both groups with 5‐year OS of 80% and 5‐year progression‐free survival (PFS) of 30% ( p  = 0.657 and p  = 0.504, respectively) with similar recurrence patterns. Conclusion: Lung resection and IGTA seem to have similar oncologic outcomes for both OS and PFS. IGTA could be an alternative effective treatment for small PM, whenever technically feasible.